Determinants of L.E.T. Performance of the Teacher Education Graduates in a State University - Pascua, Juanita B.; Navalta, Jane D. (JPAIR Multidisciplinary Research, 2011)
This study determined the correlation of personal and educational related factors with the LET performance of the Teacher Education graduates of NVSU, second semester, S.Y. 2007-2008. The respondents' personal and educational data were gathered from the Registrar's records while the result of the LET performance was taken from the PRC through the LET Review Committee. The study used descriptive survey method with the use of documentary analysis. T-test was used to determine the difference in the LET performance when grouped according to gender and degree course. F-test was used to determine if there is significant difference in LET performance and English proficiency of the respondents. Scheffe Post Hoc Test was utilized to determine the significant difference in English proficiency in terms of percentile ranks. There were more Elementary Education respondents than Secondary Education. English proficiency of respondents ranged from 23.00-73.75. There were more passers from the Elementary level than those from the Secondary level. Females' performance in LET was statistically the same with their male counterpart and that the BEEd performed better than the BSEd and all other courses combined (BSMath, BSAExt, BSHT, BSIE, BSAEd).Degree Course, GPA, English Proficiency, and Admission Test Score indicated significant relationship with LET performance.
Keywords: Licensure Examination for Teachers (LET); English proficiency; Teacher Education graduates